The Role of Trust in Mitigating Perceived Threat, Fear, and Travel Avoidance after a Pandemic Outbreak: A Multigroup Analysis - Zheng, Danni; Luo, Qiuju; Ritchie, Brent W. (Journal of travel research, 2022)
Public trust plays a vital role in a public health crisis. Drawing on trust and protection motivation theories, the study explores how people impose trust, fear and perceived threat in postpandemic travel decisions. Employing a quota sampling approach, the research collected from an online survey of 1208 respondents across regions in mainland China. Findings suggest that public trust in tourists significantly mitigates fear, perceived threat and postpandemic travel avoidance. Although trust in government can decrease travel fear, it inhibits travel intentions in a postpandemic era. The study also detects group differences by examining sociodemographic and pandemic region factors, providing practical implications on building tourists’ trust in postpandemic travel.